A Mode-Compressed Wideband Dipole Antenna Integrated With Solar Cell for Dual-Functional Operation - Wang, Heesu; Ali, Ahmed; Park, Yong Bae; Park, Ikmo (IEEE Transactions on Antennas and Propagation, 2023)
This communication presents a novel approach to integrating a wideband fat dipole antenna with a solar cell for both wireless communication and energy harvesting. The proposed design uses a uniplanar fat dipole structure incorporating a widened dipole arm and a pair of open stubs. The addition of these features compresses the first-, third-, and fifth-order modes, resulting in improved wideband characteristics and a high form factor. Moreover, integrating a dipole antenna with a solar cell provides dual functionality, enabling wireless communication, and energy harvesting from the same device. The antenna and the solar cell were designed to operate independently using RF decoupler circuits. The proposed solar cell integrated antenna achieved a wide -10-dB impedance bandwidth of 105.8% (ranging from 0.98 to 3.18 GHz), and antenna gain varied from 2.1 to 4.7 dBi within the impedance bandwidth. The whole structure has a compact size of 102 × 52 × 0.571 mm ( 0.333λ 0 × 0.170λ 0 × 0.0019λ 0 at 0.98 GHz), with a form factor of 96.2% and an optical transparency of 100%.
Keywords: Antennas measurement; Broad-band antenna; Dual function; Integrated antennas; Reflector antennas; Solar cell antenna; Wide-band; Wideband antenna; Wireless communications; Wireless energy; Dipole antenna; dual function; integrated antenna; solar cell antenna; wideband antenna